Characterization mechanical and thermal properties of modified montmorillointe clay filled polypropylene composites - Shtawa, Adel Mohamad Masod (School of Material Engineering, Universiti Malaysia Perlis, 2011)
The scope of this project is to prepare modified and unmodified montmorillonite lay filled polypropylene composites with different filler loading. The compounding have been fabricated using Z-blade mixer. In this project the testingof mechanical and thermal properties (tensile, flexural, thermogravimetric analysis (TGA), scanning electronmicroscopy (SEM), differential scanning calorimetry analysis (DSC), fourier transform-infrared spectroscopy (FTIR) and charpy impact test) will be investigated.